2022
DOI: 10.1177/09636897221077921
|View full text |Cite
|
Sign up to set email alerts
|

Celecoxib Synergistically Enhances MLN4924-Induced Cytotoxicity and EMT Inhibition Via AKT and ERK Pathways in Human Urothelial Carcinoma

Abstract: MLN4924 is a specific small-molecule inhibitor of NEDD8-activating enzyme (NAE) that blocks the neddylation modification cascade. Several I/II/III clinical trials suggested that MLN4924 exerts an antitumor effect against various malignancies. However, recent studies have also found that MLN4924 activates the PI3K/AKT and MAPK/ERK signal pathways, important regulators of tumorigenesis, and drug resistance in human urothelial carcinoma (UC). This study examined the synergistic effect of celecoxib, a cyclooxygena… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 45 publications
0
6
0
Order By: Relevance
“…In future studies, the transfection conditions and methods will be optimized to replicate the current findings in more cell lines. MLN4924 (pevonedistat) is an inhibitor of NAE, which has been widely studied in various solid tumors [33][34][35][36][37][38][39][42][43][44][45]. MLN4924 inhibited NEDDylation to play an antitumor role, and induced apoptosis, senescence, autophagy, angiogenesis inhibition, inflammatory response and chemosensitization/radiosensitization [46].…”
Section: Discussionmentioning
confidence: 99%
“…In future studies, the transfection conditions and methods will be optimized to replicate the current findings in more cell lines. MLN4924 (pevonedistat) is an inhibitor of NAE, which has been widely studied in various solid tumors [33][34][35][36][37][38][39][42][43][44][45]. MLN4924 inhibited NEDDylation to play an antitumor role, and induced apoptosis, senescence, autophagy, angiogenesis inhibition, inflammatory response and chemosensitization/radiosensitization [46].…”
Section: Discussionmentioning
confidence: 99%
“…HIGD1B deficiency notably decreased MMP levels, elevated intracellular ROS production, reduced Bcl‐2 level, and increased cleaved caspase 3 level in GC cells, suggesting that HIGD1B deficiency could lead to mitochondria‐mediated cell apoptosis in GC. Xiong et al (2022) found that inhibiting AKT and ERK signaling could induce apoptosis in urothelial carcinoma cells. Wang et al (2020) found that PP4C could inhibit lung cancer cell apoptosis via the activation of ERK signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies investigated that NAE inhibitor MLN4924 and HDAC inhibitor belinostat could interact synergistically by reciprocally disabling the DNA damage response in AML/MDS cells [ 234 , 235 ]. Guo’s group reported that the combinational of celecoxib as a cyclooxygenase-2 inhibitor with MLN4924 synergistically inhibits the survival of human urothelial carcinoma cells by decreasing phosphorylation of AKT/ERK signaling pathways [ 236 ]. Additionally, combined pharmacotherapy of MLN4924 could enhance the antitumor activity with Chk1 inhibitor, Bcl-2 inhibitor, IAP antagonist, mTOR/PI3K inhibitor, MEK inhibitor, anti-PD-L1 antibody and LSD1 inhibitor (Fig.…”
Section: Potential Development Directions Of Nae-targeting Drugs In T...mentioning
confidence: 99%